A Comprehensive Review on the Role of Genetic Factors in Neuromyelitis Optica Spectrum Disorder - Ghafouri-Fard, Soudeh; Azimi, Tahereh; Taheri, Mohammad (Frontiers in Immunology, 2021)
Neuromyelitis optica spectrum disorders (NMOSD) comprise a variety of disorders being described by optic neuritis and myelitis. This disorder is mostly observed in sporadic form, yet 3% of cases are familial NMO. Different series of familial NMO cases have been reported up to now, with some of them being associated with certain HLA haplotypes. Assessment of HLA allele and haplotypes has also revealed association between some alleles within HLA-DRB1 or other loci and sporadic NMO. More recently, genome-wide SNP arrays have shown some susceptibility loci for NMO. In the current manuscript, we review available information about the role of genetic factors in NMO.